ENSURING THE PSYCHOLOGICAL READINESS OF CHILDREN TO EDUCATION IN RURAL PRIMARY SCHOOL AS ONE OF PRIORITY DIRECTIONS OF UPDATING THE CONTENT OF EDUCATION (Pedagogy of Higher and Secondary Education, 2008)
In the article theoretical bases o f value and necessity of research o f problem in of psychological readiness of children to the studies at rural school.